The role of a new contralateral routing of signal microphone in established unilateral cochlear implant recipients. (16th September 2014) - Grewal, Amandeep S.; Kuthubutheen, Jafri; Smilsky, Kari; Nedzelski, Julian M.; Chen, Joseph M.; Friesen, Lendra; Lin, Vincent Y.W.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To investigate whether a contralateral routing of signal (CROS) microphone combined with a unilateral cochlear implant (CI) results in hearing improvement after a prolonged trial period. Study Design A prospective experimental trial was undertaken on a group of 10 postlingually deafened adults who are experienced CI users. Methods Participants completed audiometric testing and validated questionnaires with their unilateral CI alone, followed by addition of a CROS microphone (CI‐CROS). This was worn daily for the 2‐week trial, after which hearing performance was reevaluated using the same measures. Objective tests included AzBio sentences in quiet and noise and consonant–vowel nucleus–consonant (CNC) words. Subjective measures included the Abbreviated Profile of Hearing Aid Benefit (APHAB); Speech, Spatial, Qualities of Hearing Index (SSQ); Hearing Implant Sound Quality Index; an institutional questionnaire; and a daily log sheet. Results There is statistically significant enhanced speech discrimination with the CI‐CROS when speech is presented on the CROS side. However, scores are markedly diminished when background noise is introduced, particularly to the CROS side. Subjective results indicate lower satisfaction scores for the global and ease of communication subdomains of the APHAB with the CI‐CROS, but increased scores on the spatial hearing subdomain of the SSQ (P < 0.05). Conclusion The CI‐CROS provides significant benefit in certain situations, particularly speech recognition in quiet. CI‐CROS performance with background noise is poor, leading to low satisfaction scores. Further refinement of the device may yield a useful tool for unilateral CI users in the future. Level of Evidence 4. Laryngoscope, 125:197–202, 2015